Estrategias de integración para el retorno al trabajo áulico en la Educación Inicial - Guerrero Alvarado, Johanna Jael (2022)
This proposal entitled "Integration Strategies for the return to classroom work in Early Childhood Education". The objective of this proposal is the elaboration of a guide of integration strategies with creative and playful activities in order to minimize the negative socioemotional impact of the return to classroom work in Early Childhood Education with the children of the "Ramón Barba Naranjo" Educational Unit, the guide has been designed by means of a preliminary diagnosis where a mixed quali-quantitative methodological approach was used using descriptive statistics in which instruments such as the interview and the survey, Romantic pedagogical approach, were used. In addition, the guide consists of 10 activities such as stories narrated with puppets, dances, pictograms, grapho-plastic techniques, relaxation techniques and songs. The problem of the negative effects caused by the COVID-19 pandemic in educational institutions has been addressed, especially in early education, even more so when the educational authorities decided that infants must return to the classroom after several months without attending classes, It has been evidenced that it has been difficult for several infants to integrate into a classroom, due to the inadequate socioemotional development of the same, damaging the ability of socioemotional relationship with the teacher and classmates, interrupting the teaching-learning process. With this, it has been concluded that the guide is very useful for teachers, achieving the socioemotional development and adaptation of infants to the school environment after a pandemic in a novel and creative way, which also helped to create emotional bonds between teacher-infant, which has been validated by experts and users, attesting to its validity and effectiveness.